Compendium on Enterprise Resource Planning Market, Functional and Conceptual View based on SAP S/4HANA - Sarferaz, Siar. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book explains the functional scope, the data model, the solution architecture, the underlying engineering concepts, and the programming model of SAP S/4HANA as the most well-known enterprise resource planning (ERP) system. The approach is to start with general concepts and then to proceed step-by-step to concrete implementations in SAP S/4HANA. In the first part the reader learns about the market view of ERP solutions and vendors. The second part deals with the business processes for sales, marketing, finance, supply chain, manufacturing, services, procurement, and human resources which are covered with SAP S/4HANA. In the third part the underlying concepts of SAP S/4HANA are described, for example in-memory storage, analytics and search, artificial intelligence, process and data integration, security and compliance, lifecycle management, performance and scalability, configuration and implementation. The book is concluded with a final chapter explaining how to deploy an appliance to explore SAP S/4HANA. The target audience for the book are managers and business analysts who want to understand the market situation and future ERP trends, end users and process experts who need to comprehend the business processes and the according solution capabilities provided with SAP S/4HANA, architects and developers who have to learn the technical concepts and frameworks for enhancing SAP S/4HANA functionality, and consultants and partners who require to adopt and configure SAP S/4HANA.
Part 1: Market View -- 1. Challenges and Characteristics of ERP Systems -- 2. ERP Market Analysis -- 3. ERP Future Trends -- Part 2: Functional View -- 4. Functional Departments and Enterprise Domains -- 5. Master Data of Business Partner -- 6. Master Data of Product -- 7. Master Data of Bill of Material -- 8. Process of Idea to Market -- 9. Process of Source to Pay -- 10. Process of Plan to Fulfill -- 11. Process of Lead to Cash -- 12. Process of Recruit to Retire -- 13. Process of Acquire to Decommission -- 14. Process of Governance -- 15. Process of Finance -- 16. Industry Solutions -- Part 3: Conceptual View -- 17. ERP Product Qualities: Customer View -- 18. ERP Product Qualities: Provider View -- 19. In-Memory Persistency -- 20. Virtual Data Model -- 21. Transactional Programming Model -- 22. Analytics -- 23. Search -- 24. Artificial Intelligence -- 25. Internet of Things -- 26. Process Integration -- 27. Data Integration -- 28. In-App Extensibility -- 29. Side-by-Side Extensibility -- 30. User Experience -- 31. Identity and Access Management -- 32. Data Protection and Privacy -- 33. Secure Development and Operations -- 34. Globalization and Localization -- 35. Scalability and Performance -- 36. Lifecycle Management -- 37. Configuration -- 38. Implementation -- Appendix -- 39. Explore SAP S/4HANA System.
Keywords: Business information services; Application software; Business Information Systems; Enterprise Architecture; Computer and Information Systems Applications